O impacto do uso intraoperatório de opioides na sobrevida de indivíduos submetidos a cirurgia para Glioblastoma Multiforme - Naufal, Rodrigo Ferrari Fernandes (2023)
The impact of intraoperative use of opioids on the survival of individuals undergoing surgery for Glioblastoma multiforme Abstract Introduction: Glioblastoma multiforme is a primary malignant tumor of the Central Nervous System (CNS) and one of the most aggressive tumors that can affect humans, with no cure so far and with an extremely reverse prognosis with an average survival that varies from 7 to 15 months. Recently, the role of opioids used in cancer surgery, has been related to the progression and spread of the disease. The objective is to investigate the influence of intraoperative opioid use in glioblastoma surgery on disease-free survival and overall survival of these patients. Methods: Observational and retrospective study, with analysis of medical records of 133 patients who underwent 167 surgical procedures for resection of Glioblastoma Multiforme. The inclusion and exclusion criteria were as follows: patients older than 18 years of age, of both sexes, who has operated for brain tumor with anatomopathological diagnosis of glioblastoma multiforme. Patients who died in the postoperative period from causes unrelated to the underlying disease were excluded, as were patients who did not have specific data on the drugs used in the perioperative period in their records. The following variables were analyzed: onset of symptoms, age, pre-and postoperative score at Karnofsky performance scale (KPS), duration of the surgical procedure, opioid doses, overall survival and disease-free survival, gender, race, extension of surgical resection and clinical outcome after surgery. To verify the existence of a correlation between quantitative variables, Spearman Test was applied, and, for categorical (qualitative) variables, the Chi-Square Test was used. The Kruskal-Wallis test was applied to assess the variance in means between the groups. Moreover, the log-rank test was applied to assess for survival between groups. The significance level adopted in all tests was 5% (p≤0.05). This study was registered and approved by the ethical committee of the Faculdade de Medicina de Botucatu – UNESP. Results: Analyzing the correlation of the total opioid dosage and the investigated variables, the surgical duration and age at surgery (p=0.029 and 0.003, respectively) were the only ones that showed significant relations. There was no difference regarding the volume of opioids dosage and disease-free survival time (p = 0.86), or the overall survival (p = 0.87). Conclusion: The present study confirms that there is no relationship between intraoperative opioid dose and overall survival and disease-free survival in patients undergoing surgical treatment for Glioblastoma Multiforme.